2019
DOI: 10.1590/1980-5373-mr-2017-1139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sn Addition in the Microstructure Refinement and Corrosion Resistance of Cu-Zr-Al-Ag Alloy

Abstract: In this paper, a composition of known high glass-forming ability, Cu 42 Zr 42 Al 8 Ag 8 and a novel Cu 42 Zr 42 Al 8 Ag 4 Sn 4 , were produced by suction-casting. After rapid solidification of both alloys, X-ray diffraction patterns along with crystallite size estimation by Scherrer equation and scanning electron microscopy images revealed a refined microstructure, composed mainly by AlCu 2 Zr, CuZr 2 and Cu 10 Zr 7 phases. Transmission electron microscopy indicated the presence of small crystalline precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The microscopic image of the arc melted Cu45Zr45Al5Ag5 alloy ( Figure 6) presents two compounds with distinct shapes precipitated in the matrix. Different studies [5,16] reported the presence of structures similar to those presented in this research. After casting, the structure is refining, but does not substantially change (Figure 7).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The microscopic image of the arc melted Cu45Zr45Al5Ag5 alloy ( Figure 6) presents two compounds with distinct shapes precipitated in the matrix. Different studies [5,16] reported the presence of structures similar to those presented in this research. After casting, the structure is refining, but does not substantially change (Figure 7).…”
Section: Resultssupporting
confidence: 84%
“…The samples were obtained by copper mold casting and their structure and properties were investigated using X-Ray diffraction (XRD), differential scanning calorimetry (DSC) and optical microscopy.Biocompatible materials play a key role in the construction of medical devices currently used on a large scale [1][2][3][4]. Recent researches were focused on developing new materials that would not inherit the disadvantages of the classic materials (poor corrosion resistance, low deformability etc) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Bulk metallic glasses (BMG) can be a viable alternative for replacing classic biocompatible materials [18,19], due to their specific properties such as: good corrosion resistance in the absence of intercrystalline corrosion, excellent plastic deformability and good castability (absence of casting defects and voids that form when casting crystalline structure materials) even with complex geometries.…”
mentioning
confidence: 99%
See 1 more Smart Citation